DEVELOPMENT OF A DIGITAL TRACEABILITY SYSTEM IN THE COFFEE PRODUCTION CHAIN USING QR CODES - Rodrigues, Glaucione dos Santos; Balem, Fabiana Bottega (Seven Editora, 2025)
Traceability has become an essential requirement in the coffee production chain, driven by the growing demand for transparency and product quality. Small rural properties, however, face difficulties in adopting traceability technologies due to cost, limited digital infrastructure, and technical complexity. This study aimed to develop a simple and functional web system to track coffee batches using QR Codes as digital identifiers. The research followed an applied and technological approach, based on a literature review and software development. The system was implemented using the Python programming language and the Django framework, supported by an integrated database and web hosting to ensure accessibility. Simulated data representing the production process of a small rural property were used to maintain ethical compliance and avoid the need for research ethics committee evaluation. The resulting system, named RastreCoffee, enables the registration of coffee batches, recording of production information, and automatic generation of QR Codes readable by mobile devices. The results demonstrated that digital traceability can be applied to family farming in an accessible and low-cost manner. The proposed solution promotes technological inclusion, adds value to the product, and strengthens trust between producers and consumers, while also presenting potential for future enhancements.DOI: https://doi.org/10.56238/sevened2025.029-123